The role of B cell-activating factor system in autoimmune diseases: mechanisms, disease implications, and therapeutic advances - Liang Li; Shengxian Shen; Shuai Shao; Erle Dang; Gang Wang; Hui Fang; Hongjiang Qiao (Frontiers in Immunology)
The B cell-activating factor (BAFF) system, comprising two ligands and three receptors, plays a pivotal role in adaptive and innate immunity, driving autoimmunity through dysregulated B and T cell survival, differentiation, and cytokine production. This review synthesizes evidence linking BAFF system overexpression to multiple autoimmune diseases, including systemic lupus erythematosus (SLE), Sjögren’s syndrome (SS), bullous pemphigoid (BP), pemphigus vulgaris (PV), and alopecia areata (AA), where elevated BAFF system molecule levels correlate with autoantibody titers, disease activity, and post-B cell depletion relapse. BAFF-targeted therapies have demonstrated efficacy in reducing disease activity in SLE and SS. Key challenges include interspecies receptor expression discrepancies and context-dependent signalling cascades. Emerging strategies, such as sequential therapy with rituximab followed by belimumab, show promise in treating refractory autoimmune diseases such as BP and PV by counteracting the post-depletion BAFF surge. Despite progress, mechanistic gaps in BAFF-mediated crosstalk between innate and adaptive immunity, as well as interspecies-specific pathogenesis warrant further investigation using humanized disease models and single-cell transcriptomic profiling. This review underscores the therapeutic potential of BAFF system modulation while advocating for disease-specific clinical trials to optimize precision-therapeutic targeting in autoimmune diseases.